Determinación de Cyanoprokaryotas planctónicas y su potencial en la producción de cianotoxinas en un embalse de la sabana de Bogotá - Colombia (2019)
The aim of this study was to identify planktonic cyanoprokaryotic species potential producers of cyanotoxins in La Regadera dam (located at south eastern of Bogotá city) and their temporary variation for 9 months period. To accomplish the target a monthly two-phase sampling was performed; first phase took place between October and November 2015 and second phase was developed between January and July 2016. At the same time, qualitative and quantitative analysis of cyanobacterial community were developed, as well as in vitro culture of strains in BG-11 liquid and solid (agar) culture medium. Subsequently, the isolation and identification of cyanobacteria strains was carried out, as well as the molecular characterization of toxic cyanobacteria and the types of cyanotoxins expressed by them. The results showed a total of 30 isolated strains of cyanobacteria present in the dam which correspond mainly to filamentous cyanobacteria of the genus Leptolyngbya sp., Lyngbya sp., Phormidium sp., and Planktolyngbya sp. On the other hand, in March 2016 (fifth sampling) it was evidenced a Aphanizomenon gracile, algal bloom, which contains a genetic pool able to express the neutrotoxin Saxitoxine (STX), which includes the genes sxtI, sxtA and sxtG. However, none of the cyanobacterial strains in vitro cultured showed the gene regions capable of expressing the cyanotoxins, microcystin (mcyA, mcyB, mcyC, mcyD, mcyE, mcyG); cylinrospermopsin (AMT, PS, PKS), and anatoxin-a (ANAC-GENF / ANAC-GENR). These results are useful to monitoring the potential risk of toxic cyanoprokaryotic proliferation by the Water and Sewerage Company of Bogotá city and to allow implementing preventive identification and quantification protocols in order to guaranty potable water availability for human population.